2016
DOI: 10.1177/1045389x16665974
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of long-gauge carbon fiber line sensors for strain measurements in structures

Abstract: This article proposes a new technique that advances long-gauge carbon fiber line sensor technology, with and without post-tensioning of the sensor, to measure changes in strain levels in structural areas. Carbon fiber line sensors were fabricated to produce a slim high-strength sensor with a diameter of less than 1.4 mm using a carbon fiber tow with a width of 6 mm. A theoretical analysis of these sensors as well as several series of experiments was conducted to investigate the effect of fiber arrangement on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…This would lead to transverse resistance and result in nonlinear trend. This nonlinear fashion was also observed in results reported in literature in [ 9 , 25 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This would lead to transverse resistance and result in nonlinear trend. This nonlinear fashion was also observed in results reported in literature in [ 9 , 25 ].…”
Section: Resultssupporting
confidence: 88%
“…The type of carbon fibers used in the current research were carbon fiber tows or rovings which were based on a commercially available Toray T300b. The choice of Toray T300b was based on its performance in the literature [ 20 , 21 , 25 , 27 ]. Each roving contains a bundle of long strand of fibers.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…2325 It was found that the strain response and electrical properties of the long-gauge CFRP strip sensors exhibited a good linear relationship with the applied strain even at low-level strains; moreover, the proposed sensors maintain stable linearity throughout the long-term cyclic performance. Saifeldeen et al 26,27 studied the effect of fiber arrangement on the effective temperature compensation method in the smart type carbon fiber line (CFL) sensors. Moreover, in their study, a post-tensioning method was developed to straighten the skewness of fibers and control the initial creep of the CFL sensor to enhance the linearity and repeatability from low- to high-level strains.…”
Section: Carbon Fiber Sensorsmentioning
confidence: 99%
“…Continuous carbon fibers are particularly attractive due to its electromechanical behavior as well as excellent mechanical properties, in which the former makes it as a potential long-gauge sensing agent and the latter makes it as a dominant reinforcement in advanced polymer composites [ 6 , 7 ]. Polymer composites possess self-sensing functions when embedded with continuous carbon fibers, which allows the monitoring of their own conditions without the need for embedded or attached sensors.…”
Section: Introductionmentioning
confidence: 99%